MODERATING ROLE OF ONLINE TRUST ON THE RELATIONSHIP BETWEEN SERVICE DYNAMICS, INFORMATION AWARENESS, CITIZEN SATISFACTION TO E-GOVERNMENT SERVICES AND CONTINENCE INTENTION: A CASE OF UAE - Tareq Alblooshi; Mohd Faiz Hilmi; Meor Azli Ayub; Anas Abudaqa, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The purpose of this research is to examine the trends in citizen satisfaction for e-government services as observed through service usefulness, service ease of use, information awareness and service quality. Furthermore, this study also investigates the impact of citizen satisfaction towards e-government services on E-government service continuance intention. Additionally, the moderating impact of online trust on the relationship between exogenous and endogenous variables is also observed. A sample of 364 questionnaires was observed as valid enough for the purpose descriptive statistics, correlational matrix and demographic analysis as well. Additionally, this research has applied two step approach while considering the measurement model assessment and structural model assessment. The study findings through measurement model confirms that there is no problem for the model validity and reliability along with other fit indices. After examining the measurement model, structural model is applied through Smart PLS-SEM approach for both direct and moderating effect. The study results confirm that there is a significant and positive impact of e-service ease of use, information awareness, e-service quality, and online trust on citizen satisfaction to e-government services. Furthermore, the study findings confirm that there is a significant moderating effect of online trust on the relationship between e-service usefulness-citizen satisfaction, between e-service ease of use-citizen satisfaction, between information awareness-citizen satisfaction, and between e-service quality-citizen satisfaction. The study findings would be great support to various stakeholders specifically to those who are responsible for managing and providing e-government services for better citizen satisfaction. Besides, some limitations like missing of cross departmental comparison, consideration of only UAE region, and data collection through survey questionnaire only. Future studies are highly recommended to address these limitations.